From Baku to Belem: Key insights and next steps for climate and agriculture - Chevallier, Romy; Gosling, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the key insights and outcomes from the workshop From Baku to Belém: Key Insights and Next Steps for Climate and Agriculture, held on 5 March 2025. Co-hosted by the Eastern Africa Farmers Federation (EAFF) and Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), the workshop was convened in response to significant developments from the 29th Conference of the Parties (COP29) to the United Nations Framework Convention on Climate Change (UNFCCC), held in Baku, Azerbaijan, at the end of 2024. The event brought together farmers, experts, and civil society actors to unpack the implications of COP29 for African agriculture, climate ambition, and finance. In addition to analysing COP29, participants also reviewed key outcomes relevant to farmers from the other two Rio Conventions - the United Nations Convention on Biological Diversity (CBD) COP16 in Cali, Colombia, and the United Nations Convention to Combat Desertification (UNCCD) COP16 in Riyadh, Saudi Arabia. The workshop created space for reflection on the current status of agriculture in climate negotiations and key challenges and opportunities related to climate finance and broader policy engagement.